The great illusion of digital currencies - Aleksi Grym (Bank of Finland, 2018)
This paper is an analysis of digital currencies, including cryptocurrencies, and their potential as monetary instruments. The analysis shows that the concept of a digital currency is a fallacy. Currency, in the form of coins and banknotes, can be viewed as a physical representation of a monetary unit of account. Currency cannot be digitised, as this would inevitably mean creating a financial record keeping system based on accounts. Cryptocurrencies are not currencies at all but accounting systems for non-existent assets. Central bank digital currency would practically mean bank accounts at the central bank. Whether the general public should have access to such accounts, and whether monetary transactions should be allowed to be made anonymously or privately, are questions of policy and unrelated to cryptocurrencies or their underlying technology.
URN:NBN:fi:bof-201806211659
Keywords: 330; virtuaalivaluutta; kryptovaluutta; elektroninen raha